Exosomal circEhmt1 Released from Hypoxia-Pretreated Pericytes Regulates High Glucose-Induced Microvascular Dysfunction via the NFIA/NLRP3 Pathway. (18th March 2021) - Ye, Lin; Guo, Hui; Wang, Yuan; Peng, Yun; Zhang, Yongxin; Li, Shu; Yang, Meina; Wang, Ling
Abstract : Diabetic retinopathy (DR) is a frequently occurring microvascular complication induced by long-term hyperglycemia. Pericyte-endothelial cell crosstalk is critical for maintaining vascular homeostasis and remodeling; however, the molecular mechanism underlying that crosstalk remains unknown. In this study, we explored the crosstalk that occurs between endothelial cells and pericytes in response to diabetic retinopathy. Pericytes were stimulated with cobalt chloride (CoCl2 ) to activate the HIF pathway. Hypoxia-stimulated pericytes were cocultured with high glucose- (HG-) induced endotheliocytes. Cell viability was determined using the CCK-8 assay. Western blot studies were performed to detect the expression of proteins associated with apoptosis, hypoxia, and inflammation. ELISA assays were conducted to analyze the release of IL-1 β and IL-18. We performed a circRNA microarray analysis of exosomal RNAs expressed under normoxic or hypoxic conditions. A FISH assay was performed to identify the location of circEhmt1 in pericytes. Chromatin immunoprecipitation (CHIP) was used to identify the specific DNA-binding site on the NFIA-NLRP3 complex. We found that pericyte survival was negatively correlated with the angiogenesis activity of endotheliocytes. We also found that hypoxia upregulated circEhmt1 expression in pericytes, and circEhmt1 could be transferred from pericytes to endotheliocytes via exosomes. Moreover, circEhmt1 overexpression protected endotheliocytes against HG-induced injury in vitro . Mechanistically, circEhmt1 was highly expressed in the nucleus of pericytes and could upregulate the levels of NFIA (a transcription factor) to suppress NLRP3-mediated inflammasome formation. Our study revealed a critical role for circEhmt1-mediated NFIA/NLRP3 signaling in retinal microvascular dysfunction and suggests that signaling pathway as a target for treating DR.